Fatty oil from Securidaca inappendiculata exerted therapeutic effects on adjuvant-induced arthritis in mice via suppression on fibroblast-like synoviocyte - Hui Jiang; Cong-Lan Ji; Kui Yang; Wen Zhang; Jian Zuo (Kaohsiung Journal of Medical Sciences, 2018)
Securidaca inappendiculata Hassk. (SI) is a medicinal plant used to treat rheumatoid arthritis (RA) in South China. A substantial amount of fatty oil was isolated from SI (SIF), however little knowledge about its chemical composition and medicinal potentials was obtained. In this study, we analyzed its chemical composition with methyl esterification based GC–MS method, and investigated the therapeutic potentials on adjuvant-induced arthritis (AA) in mice. MTT and western-blot methods were employed to investigate its effects on proliferation rate and protein expressions in MH7A cells, respectively. It was revealed SIF was mainly comprised of saturated and monosaturated fatty acids, and the two predominant compounds were palmitic acid (36.89%) and oleic acid (31.12%). Treatment with SIF at 100 mg/kg resulted in significant alleviation of AA severity in mice, together with reduced synovial hyperplasia and inflammatory infiltration in joints, and decreased levels of sialic acid, malondialdehyde and alkaline phosphatase in serum. Results from immunohistochemical assays hinted the protective effects of SIF on joints were associated to the inhibition on production of some pathological factors in synovium, including IL-1β, TNF-α and MMP-9. SIF inhibited the proliferation of MH7A cells in a concentration dependent manner, and abrogated phosphorylation of p65 in vitro. These evidences collectively suggested SIF could suppress the pathological functions of fibroblast-like synoviocyte, and protect joints from destruction under AA conditions. Keywords: GC-MS, Chemical composition, Rheumatoid arthritis, MH7A cells